DEVELOPING READING MATERIALS FOR COMPUTER AND NETWORK ENGINEERING AT SMK SWASTA KARYA BAKTI PADANG CERMIN - Suwarni Aditya and Anni Holila Pulungan (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2017)
This research is aimed to develop reading materials as a material in teaching reading, easy to be learnt and can be used for teaching reading descriptive text. This study is developmental research uses Borg and Gall’s model. The validator of the reading materials are two experts. This instruments employed in this study are questionnaires, interview, observation, document. The finding of this study is the percentage showed that the developed reading materials were 83.2 % valid. The study takes place in SMK Swasta Karya Bakti Padang Cermin to the students of eleventh grade, academic year 2016/2017. The samples are 21 students which is given new reading materials for the research. The scoring system was based on 5 aspect they are; linguistic, process, product, content layout and suggestions. The result shows that there is an increase of students’ ability in reading descriptive text by developing reading materials as the materials in teaching reading. Therefore, the researcher suggest to English teacher to develop reading materials as one of the alternative ways to increase the students’ descriptive text in reading ability.